2020
DOI: 10.1007/s11701-020-01145-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcome measures concerning urinary incontinence after robot assisted radical prostatectomy: development and validation of an online prediction model using clinical parameters, lower urinary tract symptoms and surgical experience

Abstract: The prediction of post-prostatectomy incontinence (PPI) after robot-assisted radical prostatectomy (RARP) depends on multiple clinical, anatomical and surgical factors. There are only few risk formulas, tables or nomograms predicting PPI that may assist clinicians and their patients in adequate risk counseling on postoperative side-effects. Prospective data collection of 1814 patients who underwent RARP between 2009 and 2017 was done. Pre-operative parameters were age, body mass index (BMI), prostate volume, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…To our knowledge, only four post-prostatectomy continence recovery nomograms have been published [ 15 , 17 , 30 , 31 ]. However, all four of the nomograms have variables that may not be known preoperatively to the urologist or to the patient that involve surgical technique [ 17 , 30 , 31 ], imaging to measure urethral length [ 15 ], prostate volume [ 17 ], or surgeon volume [ 17 ]. These nomograms may be less patient-specific, more technique-dependent, and less generalizable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only four post-prostatectomy continence recovery nomograms have been published [ 15 , 17 , 30 , 31 ]. However, all four of the nomograms have variables that may not be known preoperatively to the urologist or to the patient that involve surgical technique [ 17 , 30 , 31 ], imaging to measure urethral length [ 15 ], prostate volume [ 17 ], or surgeon volume [ 17 ]. These nomograms may be less patient-specific, more technique-dependent, and less generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Collette et al [ 17 ] described a model predicting urinary continence at one year after RARP that used age, BMI, IPSS, degree of nerve sparing, prostate volume, ASA score, and surgical caseload as predictors. Matsushita et al [ 15 ] incorporated urethral length, in addition to age, BMI, and ASA score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many surgical approaches to implement RARP [83], however not enough evidence to support that these procedures are oncologically safe. The commonly used approaches are Retzius-sparing RARP which has been efficient in earlier recovery from urinary incontinence, a side effect of the surgical treatment of prostate cancer [83] [84]. Nevertheless, RARP is opted by 86% of prostate cancer patients in the United States [13].…”
Section: Prostate Cancermentioning
confidence: 99%
“…It is said that 1%–40% of patients may experience persistent urinary incontinence, 1 and 25% of PPI patients undergo surgery to improve continence 2 . Although the introduction of RARP has contributed to improvement in PPI, a recent report indicated that the 1‐ and 3‐year continent rates remained 80% and 85% 3 . Despite progress in our anatomical knowledge and surgical equipment, it cannot be said that the rate of PPI has improved significantly.…”
Section: Introductionmentioning
confidence: 99%